Bronchodilator responsiveness in children with asthma is not influenced by spacer device selection. Issue 5 (4th February 2019) - D'Vaz, Nina; Okitika, Toluwalose A.; Shackleton, Claire; Devadason, Sunalene G.; Hall, Graham L.
Abstract: Introduction: Spacer devices optimize delivery of aerosol therapies and maximize therapeutic efficacy. We assessed the impact of spacer device on the prevalence and magnitude of bronchodilator response (BDR) in children with asthma. Methods: Children with physician confirmed asthma and parentally reported symptoms in the last 12 months were recruited for this study. Each participant completed two separate visits (5‐10 days apart) with spirometry performed at baseline and following cumulative doses of salbutamol (200, 400, 800, and 200 μg) delivered by either a small volume disposable spacer or a large volume multi‐use spacer. Spacer type was alternated for each participant during each visit. The primary outcome was the effect of spacer type on bronchodilator responsiveness. The secondary outcome was to assess the relationships between spacer device, salbutamol dose and the proportion of children with a clinically relevant BDR. Results: Thirty‐two children (mean age 11.8 years) completed both visits. Change in lung function following bronchodilators was increased using the large volume spacer, for relative but not absolute increase in FEV1 [mean difference (95% confidence intervals): 1.28% (0.02, 2.54; P  = 0.047) and 0.013 L (−0.01, 0.04; P  = 0.288)], respectively. There was no observed difference in FVC by spacer type. Overall, 59% ( n  = 19) of children exhibited a clinically relevant BDR at 400 µg of salbutamol for any spacer and was independent of spacer type. Conclusion: Spacer device was not associated with clinically important differences in lung function following bronchodilator inhalation in children with asthma. At a recommended dose of 400 μg, some children with asthma may have their bronchodilator responsiveness misclassified.